Tuning the Electronic and Photonic Properties of Monolayer MoS2 via In Situ Rhenium Substitutional Doping. (16th February 2018) - Zhang, Kehao; Bersch, Brian M.; Joshi, Jaydeep; Addou, Rafik; Cormier, Christopher R.; Zhang, Chenxi; Xu, Ke; Briggs, Natalie C.; Wang, Ke; Subramanian, Shruti; Cho, Kyeongjae; Fullerton‐Shirey, Susan; et al.
Abstract: Doping is a fundamental requirement for tuning and improving the properties of conventional semiconductors. Recent doping studies including niobium (Nb) doping of molybdenum disulfide (MoS2 ) and tungsten (W) doping of molybdenum diselenide (MoSe2 ) have suggested that substitutional doping may provide an efficient route to tune the doping type and suppress deep trap levels of 2D materials. To date, the impact of the doping on the structural, electronic, and photonic properties of in situ‐doped monolayers remains unanswered due to challenges including strong film substrate charge transfer, and difficulty achieving doping concentrations greater than 0.3 at%. Here, in situ rhenium (Re) doping of synthetic monolayer MoS2 with ≈1 at% Re is demonstrated. To limit substrate film charge transfer, r ‐plane sapphire is used. Electronic measurements demonstrate that 1 at% Re doping achieves nearly degenerate n‐type doping, which agrees with density functional theory calculations. Moreover, low‐temperature photoluminescence indicates a significant quench of the defect‐bound emission when Re is introduced, which is attributed to the MoO bond and sulfur vacancies passivation and reduction in gap states due to the presence of Re. The work presented here demonstrates that Re doping of MoS2 is a promising route toward electronic and photonic engineering of 2D materials. Abstract : This work demonstrates in situ rhenium (Re) doping of synthetic monolayer MoS2 with ≈1 at% Re on r ‐plane sapphire. Electronic measurements elucidate that 1 at% Re doping achieves nearly degenerate n‐type doping, which agrees with density functional theory calculations. Low‐temperature photoluminescence measurements reveal suppression of defect emission induced by Re doping, resulting from the passivation of defects due to the presence of Re.